Oral Effects of Renal Disease: A Medical Problem in Dentistry (Bangladesh Journal of Dental Research & Education, 2014)
The number of patients with chronic kidney disease especially with diabetic nephropathy is expected to grow significantly in the future. It is associated with substantial morbidity and mortality, and the consequence of this emerging public health problem is considerable consumption of medical and financial resources. Thereby, there is a higher chance to see such patients in a dental office. People with kidney disease and those on dialysis are more likely to have periodontal disease and other oral health problems than the general population. Build up of bacteria in the mouth can cause infection. Because people with kidney disease have weakened immune systems, they are more susceptible to infections. Moreover, bone loss in the jaw can occur in those with kidney disease. Calcium imbalance contributes to loss of calcium from the bones resulting in weak bones. Weak bones can cause teeth to become loose and potentially fall out. The doctor may recommend antibiotics be taken prior to the dental procedure to help guard against infection. The purpose of this article is to evaluate oral and dental manifestations in patients on haemodialysis and kidney transplant recipients, and understanding the use and adjustment of common dental drugs which aid clinicians in safely treating these patients as well as to clarify the possible basic role in managing renal disease patients. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20253 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 70-77